Evaluation of striptillage and conventional tillage in maize production - Ferencsik, Sándor; Rátonyi, Tamás (Acta Agraria Debreceniensis, 2014)
Tillage changes soil properties and the way how the environment affects those properties. Soil properties and environment determine the rate of water movement in liquid and gaseous form into and out of soil. Based on the experimental database of the Institute of Land Utilisation, Regional Development and Technology of the University of Debrecen, Faculty of Agricultural and Food Sciences and Environmental Management and the KITE PLC, various cultivation systems were examined with maize (Zea mays L.) as indicator plant in Jász-Nagykun-Szolnok county. The sample area can be found in the outskirts of Kenderes on a meadow chernozem soil. On the examined plot, strip-tillage, subsoiling and moldboard ploughing were performed, each on 4.5 ha, respectively. The purpose of the present study is to compare these cultivation systems according to the soil- and maize kernel moisture content and to the yield based on the years of 2012 and 2013.